The Evaporation Process in a Heat Pipe: A Review Study - Ahmed, Dalal Khalid; Mahmood, Raid Ahmed (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The heat pipe is one of the efficient devices applied in industries for thermal management and energy conservation. This review outlines the evaporation process of the heat pipes, the most critical stage that will determine their thermal efficiency and operational performance. The review covers trends in the development of heat pipes regarding new materials, wick structures, and working fluids, together with the latest developments in their applications related to electronic cooling, renewable energy systems, and aerospace. It highlights the integration of CFD simulations in order to optimize heat transfer efficiency and design configurations. Experimental studies and simulations provide insight into phase-change phenomena, temperature distribution, and the impact of working fluids on evaporation dynamics. Despite significant advances, some challenges include thermal resistance, operational constraints, and inefficiencies due to nanofluids. It gives an overview of specific urgent issues that need immediate resolution to unlock the high-performance capabilities of heat pipe technology applied in sustainable and advanced thermal systems.